Answer:
I don't agree with him
Explanation:
2x = 3y
If 2x = a , 3y has to equal a
2x = a
x = a/2
3y = a
y = a/3
Therefore,
x:y = x/y
![(x)/(y) = ((a)/(2))/((a)/(3))](https://img.qammunity.org/2021/formulas/mathematics/high-school/ssb2sapame5lymc6ky3nzrjh8b3nua2sp6.png)
![((a)/(2))/((a)/(3)) = (a)/(2) . (3)/(a)](https://img.qammunity.org/2021/formulas/mathematics/high-school/6dx4j9zfrw5h608xeiwpvyxx28fpfjsmya.png)
![(a)/(2) . (3)/(a) = (3)/(2)](https://img.qammunity.org/2021/formulas/mathematics/high-school/t3lbqe9gep0nuvs130zmpquopb3oce7bko.png)
Or; If 2x = 1 , 3y has to equal 1
2x = 1 , x=1/2
3y= 1 , y=1/3
x/y = (1/2) / (1/3) = 1/2. 3/1 = 3/2
Actually, we did same thing but maybe you can understand better
so, x/y = 3/2 , not 2/3. That's why I don't agree with him
Hope this helps ^-^